Different Pharmacokinetics of Tramadol, O-Demethyltramadol and N-Demethyltramadol in Postoperative Surgical Patients From Those Observed in Medical Patients - Neskovic, Nenad; Mandic, Dario; Marczi, Saska; Skiljic, Sonja; Kristek, Gordana; Vinković, Hrvoje; Mraovic, Boris; Debeljak, Zeljko; Kvolik, Slavica (Frontiers in Pharmacology, 2021)
Most studies examining tramadol metabolism have been carried out in non-surgical patients and with oral tramadol. The aim was (1) to measure concentrations of tramadol, O-demethyltramadol (ODT), and N-demethyltramadol (NDT) in the postoperative patients after tramadol injections, and (2) to examine the effect of systemic inflammation on tramadol metabolism and postoperative pain. A prospective observational study was carried out in the surgical intensive care unit (ICU) in the tertiary hospital. In the group of 47 subsequent patients, pre-operative blood samples were taken for CYP2D6 polymorphism analysis. Systemic inflammation was assessed based on laboratory and clinical indicators. All patients received 100 mg of tramadol intravenously every 6 hours during the first postoperative day. Postoperative pain was assessed before and 30 minutes after tramadol injections. Tramadol, ODT, and NDT concentrations were determined by high-performance liquid chromatography. CYP2D6 analysis revealed 2 poor (PM), 22 intermediate (IM), 22 extensive (EM), and 1 ultrafast metabolizer. After a dose of 100 mg of tramadol, t1/2 of 4.8 (3.2 – 7.6) h was observed. There were no differences in tramadol concentration among metabolic phenotypes. The area under the concentration-time curve at the first dose interval (AUC1-6) of tramadol was 1200 (917.9 – 1944.4) μg ×h-1 ×L-1. PM had higher NDT concentrations compared to EM and IM. ODT concentrations were higher in EM, compared to IM and PM. ODT AUC1-6 was 229.6 (137.7 – 326.2) μg ×h-1 ×L-1 and 95.5 (49.1 – 204.3) μg ×h-1 ×L-1 in EM and IM, respectively (P = 0.004). Preoperative cholinesterase activity (ChE) of ≤ 4244 U L-1 was a cut-off value for a prediction of systemic inflammation. NDT AUC1-6 was significantly higher in patients with low ChE compared with normal ChE patients (P = 0.006). Pain measurements have confirmed that sufficient pain control was achieved in all patients after the second tramadol dose, except in the PM. CYP2D6 polymorphism is a major factor in O-demethylation, while systemic inflammation accompanied by low ChE has an important role in the N-demethylation of tramadol in postoperative patients. Concentrations of tramadol, ODT, and NDT are lower in surgical patients than previously reported in non-surgical patients.